Building Global Labor Solidarity in a Time of Accelerating Globalization - Dabscheck, Braham (Relations industrielles / Industrial Relations, 2016)
This article reviews the book, "Building Global Labor Solidarity in a Time of Accelerating Globalization," by Kim Scipes.